17. CURRENT SITUATION OF HOSPITAL INFECTIONS AND SOME RELATED FACTORS IN PATIENTS WITH AIRWAY INTERVENTIONS IN THE INTENSIVE CARE DEPARTMENTS OF NGHE AN OBSTETRICS AND PEDIATRIC HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: The study was conducted with the aim of describing the current status of hospital-acquired infections and some related factors in patients with airway intervention in the intensive care units of Nghe An Obstetrics and Pediatrics Hospital in 2024.Subjects and methods: Cross-sectional descriptive study with analysis on 339 patients with airway intervention.Results: Mainly patients are young and decrease by age group, in which newborns account for the highest rate of 56.6%; 45.1% of patients have respiratory diseases. The most commonly prescribed invasive procedures were 3 (39.2%); patients with mechanical ventilation and nasogastric tubes accounted for the highest proportions, 98.2% and 94.1%, respectively. The proportion of patients with hospital-acquired respiratory tract infections was 16.2%; of which the highest site of infection was pulmonary infections (42.6%), followed by blood infections (41.0%), and finally surgical site infections (9.8%) and urinary tract infections (6.6%). The causative agent of hospital-acquired infections was gram (-) with the highest proportion of 72.1%; Klebsiella aerogenes was the cause of hospital-acquired infections with the highest proportion (34.5%). Factors that increase the risk of hospital-acquired infections in patients with airway intervention include: patients who have undergone surgery, patients with central catheters.Conclusions: The rate of hospital-acquired infections in patients with airway intervention is 16.2%. The rate of children who recover from the disease is high. The main causative agents are gram (-) bacteria.
Keywords: Hospital-acquired infections; intensive care; Nghe An Obstetrics and Pediatrics Hospital